Methamphetamine Use Disorder: The Next Addiction Crisis - Paulus, Martin P. (JAMA Psychiatry, 2020)
IMPORTANCE: The prevalence of and the mortality related to methamphetamine use has doubled over the past 10 years and there is evidence suggesting that methamphetamine use disorder could be the next substance use crisis in the United States and possibly world-wide. OBSERVATION: The neurobiology of methamphetamine use disorder extends beyond the acute effect of the drug as a monoaminergic modulator and includes intracellular pathways focused on oxidative stress, neuro- and excitotoxicity, and neuroinflammation. Similarly, the clinical picture extends beyond the acute psychostimulatory symptoms to include complex cardiovascular and cerebrovascular signs and symptoms that need to be identified by the clinician. Although there are no pharmacological treatments for methamphetamine use disorder, cognitive behavioral therapy, behavioral activation and contingency management show modest efficacy. CONCLUSION AND RELEVANCE: There is a need to better understand the complex neurobiology of this disorder and to develop interventions aimed at novel biological targets. Parsing the disorder into different processes, e.g. craving or mood-related alterations, and targeting the neural systems and biological pathways underlying these processes may lead to greater success in identifying disease modifying interventions. Finally, mental health professionals need to be trained in recognizing early cardiovascular and cerebrovascular warning signs to mitigate the mortality associated with methamphetamine use disorder.